2009
DOI: 10.2298/bah0906431r
|View full text |Cite
|
Sign up to set email alerts
|

The effect of beef tallow in lamb nutrition on fattening and carcass characteristics

Abstract: Trial was carried out on 60 suckling lambs of Mis sheep population, divided into three groups. Beside milk, lambs consumed alfalfa hay and iso-protein concentrate mixtures (15% CP) ad libitum. Forage mixture I was of standard composition, whereas mixtures II and III contained 4 and 6% of beef tallow, respectively. Energy value of used mixtures I, II and III was 7,29, 7,71 and 7,94 MJ, respectively. Fattening duration was 60 days. Statistical processing of obtained data was performed using standard mathematical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…There is extremely limited work, however, on the impact of using free oil and tallow. In sheep, two studies have evaluated the effects of replacing grains with BT on growth of finishing lambs, finding variable effects of 20 and 40 g BT/kg DM on average daily gain (ADG) and feed conversion (Ružić-Muslić et al, 2009;Ahmed et al, 2015). Booyens et al (2012) also indicated the possibility of altering the FA profile of meat from lambs by feeding different sources of fat.…”
Section: Introductionmentioning
confidence: 99%
“…There is extremely limited work, however, on the impact of using free oil and tallow. In sheep, two studies have evaluated the effects of replacing grains with BT on growth of finishing lambs, finding variable effects of 20 and 40 g BT/kg DM on average daily gain (ADG) and feed conversion (Ružić-Muslić et al, 2009;Ahmed et al, 2015). Booyens et al (2012) also indicated the possibility of altering the FA profile of meat from lambs by feeding different sources of fat.…”
Section: Introductionmentioning
confidence: 99%